Preparation and Characterization of Biopolymer Electrolyte Membranes Based on LiClO4-Complexed Methyl Cellulose as Lithium-ion Battery Separator - Sun Theo Constan Lotebulo Ndruru; Deana Wahyuningrum; Bunbun Bundjali; I Made Arcana (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
The polymer electrolyte membrane is a main component of lithium-ion batteries (LiBs), serving as separator and electrolyte. In this work, we prepared biopolymer electrolyte (BPE) membranes of lithium perchlorate (LiClO4)-complexed methyl cellulose (MC). Methyl cellulose (MC), a cellulose derivative, has attractive properties for use as biopolymer electrolyte. The bulkier anion size of lithium salt (LiClO4) significantly enhances the performance of biopolymer electrolyte (BPE) membranes. The fabricated biopolymer electrolyte (BPE) membranes were characterized by FTIR, EIS, tensile tester, XRD and TGA. Biopolymer electrolyte membranes with various weight percentages of LiClO4 salt (0%, 5%, 10%, 15%, and 20%) were prepared using a simple solution casting technique. Incorporation of 10% weight of LiClO4 into the MC-based host polymer was selected as optimum condition, because this yielded good conductivity (3.66 x 10-5 S cm-1), good mechanical properties (tensile strength 35.97 MPa and elongation at break 14.47%), good thermal stability (208.4 to 338.2 °C) as well as ease of preparation and low cost of production. Based on its characteristics it can be stated that the 10% LiClO4-complexed MC membrane meets the requirements as a candidate separator for lithium-ion battery application.